2012
DOI: 10.1007/s11104-012-1498-7
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium uptake kinetics and plants factors of shoot Cd concentration

Abstract: Background and aims Accumulation of Cd in the shoots of plants grown on Cd contaminated soils shows considerable variation. A previous preliminary experiment established that one major reason for this variation was the rate of Cd influx into the roots (mol Cd cm −2 root s −1 ). However, this experiment did not distinguish between solubilization of soil Cd on the one hand and difference in Cd uptake kinetics on the other. The main objectives of the present study were thus to characterize Cd uptake kinetics of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 36 publications
5
11
0
1
Order By: Relevance
“…In this study, a significant accumulation of Cd was observed in L. chinense plants after Cd stress treatment (Figure E). This result was in accordance with previous studies that increased concentration of GSH (Figure F) was observed with the increasing Cd concentration in various plants . It has been suggested that GSH synthesis is regulated not only at the levels of enzyme activity, but also at the level of expression of GSH1 or GSHS genes .…”
Section: Discussionsupporting
confidence: 93%
“…In this study, a significant accumulation of Cd was observed in L. chinense plants after Cd stress treatment (Figure E). This result was in accordance with previous studies that increased concentration of GSH (Figure F) was observed with the increasing Cd concentration in various plants . It has been suggested that GSH synthesis is regulated not only at the levels of enzyme activity, but also at the level of expression of GSH1 or GSHS genes .…”
Section: Discussionsupporting
confidence: 93%
“…Although Cd uptake by plants is dependent on many factors including soil Cd concentrations and soil pH (Tudoreanu and Phillips, 2004), the acidifying effect of the clovers on the rhizosphere differs between species (McLay et al, 1997, Tang, 1997), and plant Cd uptake is also related to individual plant Cd uptake kinetics (Stritsis and Claassen, 2013). These species‐specific factors should be considered in future studies to better understand the plant‐specific regulators of Cd uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Например, содержание кадмия (мг/кг) составляет 0,15-0,72 для травы зверобоя; 0,05-0,36 для корней и корневищ валерианы, 0,25-0,5 для почек березы (Betulae gemmae), 0,25-0,31 для цветков бессмертника (Helichrysi arenarii flores). Следовательно, содержание данного контаминанта в ЛРП зависит в большей мере от места сбора соответствующего ЛРС, чем от морфологической части исходного ЛРС, что имеет подтверждение в современных исследованиях [14,29]. Наблюдаемая зависимость содержания кадмия от морфологической части растений в ранних исследованиях [28,30], по-видимому, связана с тем, что кадмий вносился в почву в легкодоступной для растений форме.…”
Section: Fig 2 Content Of Cadmium In the Herbal Medicinal Products unclassified